Kineziterapijos taikymas nudegimų traumos ūmiuoju ir chirurginio gydymo laikotarpiais: literatūros apžvalga - Siparytė-Sinkevičienė, Brigita; Rimdeika, Rytis (Lietuvos chirurgija, 2020)
People recovering from burn injury experience a wide range of challenges throughout their recovery. Currently, the survival is not the only important issue in the treatment of burns. As the advancement and amelioration in burn treatment have improved significantly, the patients’ recovery and abilities to return to their pre-burn functional status are of equal importance as well. The results of recent scientific literature review (Kazis et al.) demonstrate that 28% of burn survivors never return to any form of employment and only 37% of burn survivors regain the fullness of previous employment. Physical therapy is a critical, though painful, component of burn rehabilitation therapy and includes a variety of physiotherapy treatment methods such as exercise therapy, cardiopulmonary training, joint mobilization, positioning, splint adjustment, etc. The application of physiotherapy after burn injury was found to improve physical capacity, muscle strength, body composition, and quality of life. The use of early physiotherapy is also recommended in patients treated in the intensive care unit.
Keywords: nudegimų trauma; kineziterapija; pratimai; raumenų jėga